Materializing corporate social responsibility in investor-state dispute settlement - Tomoko Ishikawa (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
Despite its oft-claimed voluntary nature, corporate social responsibility (CSR) has increasingly interacted and been integrated with legal obligations, and circumstances have arisen wherein a corporation's breach of CSR has caused legal responsibility. This Perspective discusses host countries' options for pursuing an investor's CSR-based responsibility through counterclaims in investor-state dispute settlement.
Keywords: 330